Extraordinary Jane - Harrison, Hannah E. (New York , NY: Dial Books for Young Readers, 2014)
"Jane the dog doesn't have a unique talent in the circus like the rest of her family, until the ringmaster discovers what is truly special about her"--Provided by publisher.
Accelerated Reader AR